The microstructure of pollen grain in tea (Camellia sinensis) pollen and bee bread - SU Song-kun; CHEN Sheng-lu (浙江大学学报. 农业与生命科学版)
There were no evidences of damage to pollen wall and the structure of tea pollen and bee bread by observation under optical microscope and scanning electrical microscope. In the experiments of in vitro analogic digestion, the amount of inclusion outer-vomiting pollen particles (IOVPP) in bee bread was more than that in corbicular pollen. Furthermore, the amount of IOVPP in bee bread increased with prolongation of the ferment time. The result indicated that bee bread was more readily digestible than bee pollen.